ENGLISH PHONEMES AND THEIR CLASSIFICATION: A THEORETICAL OVERVIEW - Shakhlokhon Karimjonova Rashidjonovna; Minojiddinova Mukhlisa Ahrorjon qizi (Ustozlar uchun, 2025)
This article provides a comprehensive theoretical analysis of phonemes in English and their classification. The role of the concept of phoneme in linguistics, one of its main features - the meaning-differentiating property, and its function in pronunciation are explained in detail. Vowel and consonant phonemes in English are divided into classes according to articulatory and acoustic criteria. The article analyzes the realization of phonemes in pronunciation, their segmental and suprasegmental properties (stress, intonation, rhythm), and their role in the speech process. Some comparative aspects of English phonemics with other languages, in particular, the Uzbek language, are also considered. The results of the study serve not only to deepen theoretical knowledge in the field of phonetics and phonology, but also to develop phonetic competence in the process of teaching and learning English.